Achieving Demand-Side Synergy from Strategic Diversification: How Combining Mundane Assets Can Leverage Consumer Utilities - Ye, Guangliang; Priem, Richard L.; Alshwer, Abdullah A. (Organization Science, 2012)
We explore the overlooked issue of how certain strategic-level, interindustry diversification options might increase consumer utility. Discussions of inter-industry diversification typically focus on producer synergies obtainable from economies of scope or from skill transfer across business units. Discussions of intra-industry product diversification—generally, the province of marketing—typically focus on synergies obtainable from product bundling, which lowers producer costs or provides convenience for consumers. We take a different tack by linking interindustry diversification and consumer utility. We first separately examine two possible consumer benefits of interindustry diversification: (1) facilitating consumers' accomplishment of two tasks simultaneously or (2) attracting diverse consumer groups to a common platform when intergroup externalities exist. We then assess a simple empirical context that shows potential for simultaneous consumer utilities and two-sided market utility together. We analyze this context and concurrently develop a mathematical model showing how these demand-side synergies can create unique business value. We next introduce asymmetric preferences among consumer subgroups, and we refine our arguments by comparing their conclusions with the empirical data. We learn that combinations of otherwise mundane (i.e., commonplace) assets can create consumer value—“superior” assets are not necessary. Moreover, common ownership is necessary for the pricing flexibility required to deliver (and capture) maximum value through interindustry diversification, especially when consumer groups' preferences may change; the negotiations and settling up required for cooperation through alliances will, without common ownership, increase costs and reduce responsiveness. We discuss the sustainability of demand-side advantages and the implications of these ideas for future research and practice.